Effectiveness of Discharge Instruction on Mobile Application toward Knowledge and Care Practice of Caregivers of Patients with Low Risk Mild Traumatic Brain Injury before Discharge from Emergency Department - Binsa, Fursan; Khupantavee, Natenapha; Naka, Kanittha (Princess of Naradhiwas University Journal, 2023)
This quasi-experimental study aimed to determine the effectiveness of discharge instruction on mobile application toward knowledge and care practice of caregivers of patients with mild traumatic brain injury in low risk before discharge from emergency department in the lower-southern provinces. Purposive sampling was used to select 50 participants into the study. The participants were divided into two groups; 25 participants per group. The control group received usual nursing care, whereas the experimental group received discharge instruction through mobile application. The research instruments consisted of mobile application, a questionnaire asking about knowledge and a questionnaire asking about care practice which the the questionnaires received the reliability KR20 at .82 and .84, respectively. The data were analyzed using descriptive statistics, dependent t-test and independent t-test. The study results showed as follows: (1) The mean score of using mobile application in the experimental group was significantly higher than before using the mobile application (t= 13.52, p < .05) (2) The mean score of caregivers’ knowledge and care practice for patients with mild traumatic low risk brain injury in the experimental group was significantly higher than the control group (t = 19.90, p <. 05) and (3) The mean score of the 24-hour post-injury care practice in the experimental group using mobile application was significantly higher than the control group receving usual care (t = 15.13, p < .05). The results also showed that using mobile application enabled caregivers to provide better care for the patients. Therefore, it is suggested for nurses to use this application as a part of the patient care; recommend to caregivers to observe and track the patients’ conditions at home.